REPRODUCTIVE SYSTEM of Mimosa scabrella IN CONSECUTIVE REPRODUCTIVE EVENTS IN THE MOUNTAINOUS REGION OF SANTA CATARINA STATE - Arruda, Guilherme Oliveira Santos Ferraz de; Mantovani, Adelar; Montagna, Tiago; Bernardi, Alison Paulo; Costa, Newton Clóvis Freitas da; Reis, Maurício Sedrez dos (Floresta, 2020)
The reproductive system determines evolutionary inheritance of populations by establishing patterns of gametes union to originate the next generation. The objective of this study was to investigate the mating system of Mimosa scabrella Benth. (bracatinga), a Brazilian tree species with socioeconomic and ecological importance, in a population of the mountainous region of Santa Catarina state, in two consecutive reproductive events. The analyzes in the 2015 and 2016 reproductive events were lead with isoenzymatic markers and the mating system characterization was performed based on mixed crosses and correlated crosses models, and the means of each parameter were statistically compared. Among the results, the multilocus outcrossing rates (tm(2015): 0.925 and tm(2016): 0.845) showed high magnitude and differed from the unit; the self-fertilization rates were significantly different from zero (s (2015): (0.075 and(2016): 0.155) indicating that the species does not show self-incompatibility. In addition, the positive outcrossing rates among relatives (tm-ts(2015): 0.142 and tm-ts(2016): 0.170) suggest inbreeding crosses in the population. The highest proportions in offspring were half-sibs (2015: 0.736 and 2016: 0.579), suggesting predominance of randomness at crossings. From this it is concluded that M. scabrella has a mixed mating system, with predominance of crossing at population level.